Biological Markers to Detect Periodontal Severity in Postmenopausal Women: A Systematic Review - Megawati; Pitu Wulandari; Lutfi Putra Perdana (Dentika: Dental Journal, 2026)
Periodontal disease is a significant health concern, particularly in postmenopausal women due to hormonal changes affecting immune response and bone metabolism. This study reviews non-invasive biomarkers for detecting and monitoring disease severity through a literature search in PubMed, Cochrane Library, and Science Direct (2015–2025). Five studies found that biomarkers such as salivary cytokines, calcium, estradiol, calprotectin, and serum markers are significantly associated with periodontal clinical parameters. These biomarkers show potential for early detection and personalized management, although further research is still needed.